Investigation on Properties of ECC Incorporating Crumb Rubber of Different Sizes - Zhang, Zhigang; Ma, Hui; Qian, Shunzhi (Journal of Advanced Concrete Technology, 2015)
In the past decades, incorporating crumb rubber into concrete has attracted attention in the field of building materials due to the properties improvement it brought. In this study, crumb rubber of two particle sizes (40CR and 80CR, which have a sieve size of 400 μm and 220μm, respectively) is incorporated into engineering cementitious composite (ECC) material to replace silica sand. Furthermore, three different replacement percentages (0, 15%, 25% by volume) for each crumb rubber size are conducted in this study. The influence of crumb rubber on the ECC is revealed via density, compressive strength, flexural performance, drying shrinkage, restrained shrinkage and environment footprint. The experimental results show that the incorporation of crumb rubber into ECC increases bending deformation capacity, decrease density and compressive strength. While the free drying shrinkage of ECC increases with the addition of crumb rubber, lesser crack number, crack width and cracking tendency were found in the restrained ring test when compared to ECC without crumb rubber. In terms of crumb rubber size, ECC with smaller crumb rubber appear to have lower density and higher bending defamation capacity and shrinkage than those with larger crumb rubber. In addition, incorporating crumb rubber into ECC reduces CO2 emission, thus improve the greenness of ECC to a certain degree.